Synergistic regulation of Rgs4 mRNA by HuR and miR-26/RISC in neurons. Issue 7 (3rd July 2021) - Ehses, Janina; Fernández-Moya, Sandra M.; Schröger, Luise; Kiebler, Michael A.
ABSTRACT: The negative regulator of G-protein signalling 4 (Rgs4) is linked to several neurologic diseases, e.g . schizophrenia, addiction, seizure and pain perception. Consequently, Rgs4 expression is tightly regulated, resulting in high mRNA and protein turnover. The post-transcriptional control of gene expression is mediated via RNA-binding proteins (RBPs) that interact with mRNAs in a combinatorial fashion. Here, we show that in neurons the RBP HuR reduces endogenous Rgs4 expression by destabilizing Rgs4 mRNA. Interestingly, in smooth muscle cells, Rgs4 is stabilized by HuR, indicating tissue-dependent differences in HuR function. Using in vitro RNA-based pulldown experiments, we identify the functional AU-rich element (ARE) within the Rgs4 3ʹ-UTR that is recognized and bound by HuR. Bioinformatic analysis uncovered that this ARE lies within a highly conserved area next to a miR-26 binding site. We find that the neuronal-enriched miR-26 negatively influences Rgs4 expression in neurons. Further, HuR and miR-26 act synergistically in fluorescent reporter assays. Together, our data suggest a regulatory mechanism, in which an RBP selectively destabilizes a target mRNA in cooperation with a miRNA and the RISC machinery.